2017
DOI: 10.18103/mra.v5i5.1243
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of cancer immunity-inducing effect by pH-sensitive polysaccharide-modified liposomes with combination of TGF-β type I receptor inhibitor-embedded liposomes

Abstract: Recent success of immune checkpoint inhibitors has revealed that canceling of immunosuppression in tumor microenvironments is crucially important to achieve effective cancer immunotherapy using tumor-specific cytotoxic T lymphocytes (CTLs). Transforming growth factor (TGF)- signaling also contributes to immunosuppression in tumors via inactivation of CTL and activation of regulatory T cells. The combination of the CTL induction system and blocking system of TGF- signaling is attempted in this study using ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Combination delivery of IL-2 and inhibitor of TGF- type I receptor using poly(ethylene glycol)-modified liposomes encapsulating nanogel increase CD8-positive T cells and NK cells in tumor and cancer therapeutic effect was also improved strongly (Park et al, 2012). Combination of PEG-modified liposome embedded the inhibitor of TGF- type I receptor with pH-sensitive dextran-modified liposomes encapsulated antigenic proteins also strongly increased their immunotherapeutic effects by increased infiltration of CD8-positive T cells into tumor tissues (Yuba et al, 2017b). These reports indicate the importance of regulation of TGF- signaling in tumors for liposome-based immunity-inducing system.…”
Section: Cancellation Of Immunosuppressionmentioning
confidence: 98%
“…Combination delivery of IL-2 and inhibitor of TGF- type I receptor using poly(ethylene glycol)-modified liposomes encapsulating nanogel increase CD8-positive T cells and NK cells in tumor and cancer therapeutic effect was also improved strongly (Park et al, 2012). Combination of PEG-modified liposome embedded the inhibitor of TGF- type I receptor with pH-sensitive dextran-modified liposomes encapsulated antigenic proteins also strongly increased their immunotherapeutic effects by increased infiltration of CD8-positive T cells into tumor tissues (Yuba et al, 2017b). These reports indicate the importance of regulation of TGF- signaling in tumors for liposome-based immunity-inducing system.…”
Section: Cancellation Of Immunosuppressionmentioning
confidence: 98%
“…Recently, Yuba E et al studied the strong immunotherapeutic effect of pH-sensitive dextran liposomes modified with PEG as well as TGF-β 1 (transforming growth factor) receptors. The liposome delivery resulted in a high antitumor effect by the infiltration of CD8-positive cells to the tumor [74]. Yuba et al reported that liposomes modified with pH-sensitive polymers such as curdlan and mannan were used as bioactive polysaccharides.…”
Section: Bioactive Nanoparticles For Cancer Immunotherapymentioning
confidence: 99%